Service quality and customer loyalty in hotels within Ibadan metropolis, Oyo State (2019)
The study assessed the effect of service quality on customers’ loyalty in hotels within Ibadan metropolis. Random and convenience sampling was used to sample 192 respondents from thirteen hotels in four local government areas within Ibadan metropolis. Data were analyzed using descriptive and inferential statistics. The findings revealed that there was an overall statistically significant correlation between service quality and overall loyalty (r = 0.439, p<0.01), word of mouth (r = 0.427, p< 0.01) and repeat patronage (r= 0.443, p< 0.01), there was no significant relationship between service quality and price insensitivity (r = 0.439, p>0.01). Overall expectation towards tangibility was at the agree level (4.18) while perception was ranked at the strongly agree level (4.24 )and (4.22), overall expectation towards reliability is at the agree level (4.06) and responsiveness was at the agree level (4.17), perception of responsiveness dimension was at the strongly agree level (4.26), overall expectation towards assurance was at the agree level (4.12), perception of assurance dimension was ranked at the agree level (4.19) and empathy dimension was ranked at the strongly agree level (4.29), while overall expectation towards empathy was at the agree level (4.27). There was significant relationship between service quality and customer loyalty.